High-Resolution Ultrasound-Guided Perforator Mapping and Characterization by the Microsurgeon in Lower Limb Reconstruction - Kehrer, Andreas; Heidekrueger, Paul I.; Lonic, Daniel; Taeger, Christian D.; Klein, Silvan; Lamby, Philipp; Sachanadani, Neil S.; Jung, Ernst Michael; Prantl, Lukas; Batista da Silva, Natascha Platz (Journal of Reconstructive Microsurgery, 2020)
Background Preoperative ultrasound (US)-guided perforator mapping has immensely simplified perforator flap planning. It may be executed by the microsurgeon. Device settings and selection of ultrasound modes are of utmost significance for detection of low-flow microvessels. The following study evaluates different US modes.Methods A prospective complete data acquisition was performed from July 2018 to June 2019 in a subset of patients who underwent US-guided flap planning. Multifrequency linear transducers were used applying five US modes. Brightness (B)-mode, color flow (CF), power Doppler (PD), pulse wave (PW), and B-flow modes were evaluated regarding applicability by microsurgeons. Peak systolic velocity (PSV), end diastolic velocity (EDV), and resistance index (RI) were chosen to evaluate flow characteristics. US results were correlated to intraoperative findings.Results A total number of eight patients (six males and two females) undergoing anterolateral thigh (ALT) or superficial circumflex iliac artery perforator (SCIP) flap surgery received an extensive standardized US-guided perforator characterization. Qualitative evaluation was performed in B-mode, color-coded duplex sonography (CCDS), PD, and B-flow mode. Quantitative assessment was executed using PW-mode and CCDS measuring the microvessels' diameter (mm) and flow characteristics (PSV, EDV, and RI). CCDS provided a mean diameter of 1.93 mm (range: 1.2–2.8 ± 0.51), a mean systolic peak of 16.9 cm/s (range: 9.9–33.4 ± 7.79), and mean RI of 0.71 (range: 0.55–0.87 ± 0.09) for lower limb perforators. All perforators located with US were verified by intraoperative findings. An optimized, time-effective US mapping algorithm was derived. Qualitative parameters may be evaluated with B-mode, CF, or B-flow. Smallest microvessels may be assessed in PD-mode. Lowering pulse-repetition frequency (PRF)/scale is mandatory to image low-flow microvessels as perforators. Quantitative information may be obtained using PW-mode and the distance-measuring tool in CF-mode. Image and video materials are provided.Conclusion CCDS proved to be a powerful tool for preoperative perforator characterization when using a structured approach and mapping algorithm. Different techniques may be applied for specific visualizations and performed by the microsurgeon.
Keywords: ultrasound; perforator flap; color coded duplex ultrasound